Let, show that (aI + bA)n = anI + nan-1bA, where I is the identity matrix of order 2 and n ϵ N.
To prove: (aI + bA)n = anI + nan-1bA
Proof: Given A
We will be proving the above equation using mathematical induction.
Steps involved in mathematical induction are-
1. Prove the equation for n=1
2. Assume the equation to be true for n=k, where k ϵ N
3. Finally prove the equation for n=k+1
I is the identity matrix of order 2,
i.e. I
Let P(n): (aI + bA)n = anI + nan-1bA, n ϵ N
For n=1,
L.H.S: (aI + bA)1 = aI + bA
R.H.S: a1I + 1a1-1bA= aI + a0bA= aI + bA
So, L.H.S = R.H.S
∴ P(n) is true for n=1
Now assuming P(n) to be true for n=k, where k ϵ N
P(k) : (aI + bA)k = akI + kak-1bA …… (1)
Now proving for n=k+1, i.e. P(k+1) is also true
L.H.S = (aI + bA)k+1
= (aI + bA)k . (aI + bA)1
= (akI + kak-1bA). (aI + bA) ……from (1)
= aI(akI + kak-1bA) + bA(akI + kak-1bA)
= aI(akI) + aI(kak-1bA) + bA(akI) + bA(kak-1bA)
= (a.ak) (I×I) + kb(a.ak-1)(IA) + (bak)(AI) + (bb) kak-1(AA)
= ak+1 I2 + ka1+k-1 bA + bakA + b2kak-1A2 (IA = AI= A & I2 = I)
= ak+1 I + kak bA + bakA + b2kak-1A2
Calculating A2
A2 = A.A
∴ A2 = O (O is the null matrix)
Putting value of A2 in L.H.S
L.H.S = ak+1 I + kak bA + bakA + b2kak-1(O)
= ak+1 I + kak bA + bakA + 0
= ak+1 I + kak bA + bakA
= ak+1 I + (k+1)ak bA
Putting n=k+1 in R.H.S
R.H.S = ak+1 I + (k+1)ak bA
∴ L.H.S = R.H.S
All conditions are proved. Hence P(k+1) is true.
∴ By mathematical induction we have proved that P(n) is true for all n ϵ N.
Thus, (aI + bA)n = anI + nan-1bA, where I is the identity matrix of order 2 and n ϵ N.